Characteristics and multi-omics analysis of spontaneous spondyloarthritis in non-human primates: Case report - Lei Cai; Qing Lv; Ronghua Ma; Wei Liu; Yalun Guan; Zhongqiang Huang; Qingyu Liu; Yunfeng Li; Shuhua Liu; Ge Li; Yu Zhang (Heliyon)
Spondyloarthritis is a prevalent and persistent condition that significantly impacts the quality of life. Its intricate pathological mechanisms have led to a scarcity of animal models capable of replicating the disease progression in humans, making it a prominent area of research interest in the field. To delve into the pathological and physiological traits of spontaneous non-human primate spondyloarthritis, this study meticulously examined the disease features of this natural disease model through an array of techniques including X-ray imaging, MRI imaging, blood biochemistry, markers of bone metabolism, transcriptomics, proteomics, and metabolomics. X-ray imaging results revealed that crab-eating monkeys (Macaca fascicularis) with spontaneous spondyloarthritis developed bone spurs in the spine and experienced bone destruction in peripheral joints. MRI imaging further confirmed inflammatory changes in the spine and facet joints of these monkeys, along with inflammation and bone destruction in peripheral joints. Blood biochemistry analysis showed abnormalities in liver function and kidney function indicators in crab-eating monkeys with spontaneous spondyloarthritis. Analysis of bone metabolism-related markers showed a decrease in bone formation (BGP) and bone resorption (β-CTx). A thorough correlation analysis was conducted on the transcriptome and proteome expression data, revealing a significant positive correlation between the two datasets. A total of eight genes and proteins with high expression levels were identified as common to both the transcriptome and proteome. Subsequent Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses were performed on these co-expressed genes and proteins, indicating a predominant enrichment in the IL-17 signaling pathway, with S100A8 and S100A9 identified as the core proteins. Further analysis using clinical data in conjunction with proteome data through Weighted Gene Co-expression Network Analysis (WGCNA) demonstrated a significant positive correlation between the high expression of S100A8 and S100A9 and the clinical phenotypes of spinal abnormalities, thereby corroborating the close association of S100A8 and S100A9 with the phenotype of spondyloarthritis. Human clinical studies have already established a link between S100A8 and S100A9 and autoimmune-related arthritic diseases, suggesting that the spontaneous spondyloarthritis observed in crab-eating macaques may be related to autoimmune diseases. It is hypothesized that S100A8 and S100A9 could serve as potential predictive biomarkers for spondyloarthritis in non-human primates.